2000
DOI: 10.1074/jbc.275.6.3767
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of a Peptide Identified as a Functional Element in αA-crystallin

Abstract: Eye lens ␣-crystallin is a member of the small heat shock protein (sHSP) family and forms large multimeric structures. Earlier studies have shown that it can act like a molecular chaperone and form a stable complex with partially unfolded proteins. We have observed that prior binding of the hydrophobic protein melittin to ␣-crystallin diminishes its chaperone-like activity toward denaturing alcohol dehydrogenase, suggesting the presence of mutually exclusive sites for these proteins in ␣-crystallin. To investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
234
1
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 195 publications
(249 citation statements)
references
References 42 publications
12
234
1
2
Order By: Relevance
“…We identified 19-to 20-mer sequences with chaperone function from aA-crystallin and aB-crystallin. 12,13 The individual amino acid, the location, and the chain length of the amino acid sequence are important determinants of the function of a specific peptide. For example, while a 19-mer peptide consisting of a 70 to 88 sequence of aA-crystallin is antiapoptotic, sequences 66 to 80 of a 15-mer peptide cause aggregation and toxicity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We identified 19-to 20-mer sequences with chaperone function from aA-crystallin and aB-crystallin. 12,13 The individual amino acid, the location, and the chain length of the amino acid sequence are important determinants of the function of a specific peptide. For example, while a 19-mer peptide consisting of a 70 to 88 sequence of aA-crystallin is antiapoptotic, sequences 66 to 80 of a 15-mer peptide cause aggregation and toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…11 Potential sequences of a-crystallins that exhibit chaperone activity have been identified. 12,13 We previously identified a 19-mer sequence corresponding to beta3 and beta4 regions of aA-crystallin domain, which has similar chaperone activity in vitro to that of aA-crystallin. 12 Further studies have revealed that the 19-mer peptide sequence of aA-crystallin inhibits fibril formation of Ab-amyloid peptides and suppresses the toxic action of Ab-peptide in rat pheochromocytoma (PC12) cells.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This part of Hsp21 is a disordered, methionine-rich domain and has previously been suggested to be substratebinding (Harndahl et al 2001). For other sHsps, the Nterminal region has also previously been shown to be implicated in substrate-binding (Jaya et al 2009;Sharma et al 2000). Residues M1 and K27, and K18, are the only aminegroup-containing amino acid residues out of the 81 amino acid residues in the disordered N-terminal region of wild- Fig.…”
Section: Frequency Of the Different Hsp21 And Mdh Residues Involved Imentioning
confidence: 99%
“…Recent advances in NMR spectroscopy, such as the development of Transverse Relaxation Optimized SpectroscopY (TROSY) methods, may provide a route to determine the structures of these large chaperone aggregates [34]. It would also be valuable to determine the chaperone binding site(s) in clusterin; this might be accomplished via cross-linking studies with bound target peptides and proteins, as has been done for sHsps [8,35]. Furthermore, the hypothesis that subunit exchange is a crucial factor in the activation of clusterin chaperone action could be tested by directly measuring the rate of clusterin subunit exchange and its variation with pH, temperature and the presence of target protein.…”
Section: Unanswered Questions and Directions For Shsp And Clusterin Rmentioning
confidence: 99%